Multilingualism in opera production, reception and translation - Mateo, Marta (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Despite the significant presence of multilingualism in both opera production and reception as well as in the context of opera translation, the coexistence of different languages in the world of opera has only sporadically received any research attention, either from musicologists or translation scholars. After a brief discussion of the problematic language issue in the history of opera, this article will examine the multilingualism which marks the genesis of opera texts and many opera productions. Next, it will present different types of multilingualism in opera pieces, with examples of each type. Finally, it will study the relationship between translation and multilingual operas from different standpoints, including a brief analysis of the plurilingual reception context often created by the various translation modalities applied to opera works. A descriptive and contextual approach will mainly be used in this study, which aims to do justice to the presence of multilingualism in the opera house, in both source and target contexts, as well as to encourage further research on this topic within Translation Studies.